Identification and Treatment for Depressive Disorder: Descriptive Study from Indonesia - Dharmady Agus; Hardi, Nicholas; Fransisca Theresia; Aila Johanna; Rima Sisca Fanuela; Ika Suswanti (Jurnal Kesehatan Masyarakat, 2025)
Access to professional mental health services was low worldwide, especially in lower-middle-income countries. Indonesia encounters several challenges in providing adequate mental health care. Poor detection could reduce the treatment coverage. This study aimed to determine how many individuals with depression recognize their condition or receive an appropriate diagnosis, as well as the types of treatments they receive. We analyzed secondary data from the Indonesian Family Life Survey 5th edition (IFLS-5), which included socio-demographic data, levels of well-being, subjective experiences of mental health issues, and treatment information. We found that 6,645 respondents (22.8%) exhibited significant depressive symptoms, yet only 15 respondents (0.1%) reported having a lifetime psychiatric disorder that met the criteria for depression. Most lifetime psychiatric diagnoses (LPD) were made by doctors (93.3%). A significant portion of respondents with a history of psychiatric disorders did not receive any treatment (70.5%), and among those who did, medication was the most common approach. There was considerable gap between the identified significant depressive symptoms and LPD, warranting further exploration. Low detection rates and stigma, potentially linked to Indonesian culture and perceptions of mental health, may underlie these issues. A variety of treatment options must be available and accepted to be beneficial for patients.